A plant traits approach to managing legacy species during restoration transitions in temperate eucalypt woodlands. Issue 3 (1st February 2016) - Cole, Ian A.; Prober, Suzanne M.; Lunt, Ian D.; Koen, Terry B.
Abstract : Degraded communities often contain a subset of the species that comprised the predisturbance community. These represent an important legacy of the predisturbance state, yet restoration treatments may be detrimental to them. This study examined the potential of leaf traits and life form to predict whether restoration treatments can maintain legacy swards of Austrostipa bigeniculata (hereafter Austrostipa ) while controlling exotic annuals in temperate eucalypt woodlands. Treatments included carbon addition to reduce soil nitrate, both with and without burning or pulse grazing to deplete exotic seed pools. We compared leaf traits of Austrostipa with a native grass ( Themeda triandra ) known to be advantaged, and 8 exotic annual species known to be disadvantaged by these treatments. Leaf traits indicated potentially greater negative impacts of carbon addition on exotic annuals compared to Austrostipa, and on Austrostipa compared to Themeda, suggesting a net restoration benefit. Similarly, burning or pulse grazing is expected to have little negative impact on perennial resprouting grasses (hemicryptophytes; Austrostipa and Themeda ) compared with annual exotics (therophytes) with short‐lived seed banks. Treatment responses were largely consistent with predictions: treatments that significantly reduced exotic annuals had no net disadvantage to Austrostipa swards despite significant reductions in Austrostipa seedling growth with carbon addition. Indeed by Year 3, Austrostipa mortality in untreated plots led to 46% lower Austrostipa abundance than in treated plots at one site, potentially due to litter build‐up or other mechanisms. We conclude that plant traits provide a useful framework for designing restoration transitions that retain native legacy species while controlling exotics.